Interventional treatment of para-valvular leaks after prosthetic valve replacement with plug devices -first results from a prospective registry. (14th October 2021) - Zahn, R; Kment, H; Schofer, J; Lubos, E; Geist, V; Eggebrecht, H; Butter, C; Wolf, A; Schaefer, U; Schumacher, B; Schneider, S
Abstract: Background: Interventional closure of symptomatic paravalvular leaks (PVL) after surgical or interventional valve replacement by plug implantation has emerged as an alternative to surgical correction, which is associated with high morbitity and mortality rates. To date, data on procedural efficacy and clinical outcome after transcatheter closure with plugs is sparse, especially prospective data are missing. Methods: We analysed data from a multi-center prospective registry on interventional PVL closure with plug devices. Results: Between 06/2012 and 04/2020 55 interventions were performed with different numbers of plugs (maximal 4) in 51 patients at 9 hospitals. Interventions were performed in 15 women and 36 men at high surgical risk for repeat surgery. 48% of procedures were performed for mitral PVLs and 52% procedures were performed for aortic PVLs. Mean age of the population treated was 69±13 years and mean log. Euro-Score I was 22.5±14.2%. Patients were treated by implantation of Amplatzer Vascular Plug III (80%) and Occlutec occluders (9%). Aortic PVLs were treated using a retrograde transfemoral access, mitral PVLs were treated using either a transseptal (25/26) or transapical access (1/26) with 3-dimensional transesophageal echocardiographic and fluoroscopic guidance. Indication for PVL closure was previous surgery (n=39), high-risk patients (n=24), heart failure (n=22), age (n=20) and hemolysis (n=12). 40 patients had NYHA class III/IV at admission. Interventional closure of PVL was completely successful in 40 procedures (73%), partially successful in 7 procedures (13%) and failed in 7 procedures (13%). NYHA class I/II after PVL closure was achieved in 75% patients. However, 8 out of 12 patients with hemolysis as indication still hemolyzed at discharge. Complications occurred in 16% of patients. In-hospital mortality rate was 4% of procedures (2/51). After hospital discharge no death occurred during 30-day follow-up. Conclusions: In this prospective interventional PVL registry inclusion rate was lower than expected. There was an equal distribution of aortal and mitral PVLs. At least partial success could be achieved in 86% of patients, with significant functional improvement in most patients. In this high risk population hospital mortaliy was low (4%), indicating that interventional PVL treatment should be the treatment of choice, when discussed by a heart team. Funding Acknowledgement: Type of funding sources: None.